Academic Library consortia in Vietnam: Historical Context, current state and the prospect for development - Hoang Thi, Thuc (Curtin University, 2015)
This research investigates whether Vietnam—a developing country with limited experience of library cooperation—is able to use consortia as a means of improving access to academic library content and services. The research uses a mixed methods approach, consisting of a questionnaire and interviews, to collect data addressing the research question: Are library consortia suited as a means of cooperation by Vietnamese academic libraries, and if so how can they be successfully developed and implemented?